2011
DOI: 10.1063/1.3671404
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of thermomigration of Sn atoms to the hot end of 96.5Sn-3Ag-0.5Cu flip chip solder joints

Abstract: In this study, we investigated the phenomenon of thermomigration in 96.5Sn-3Ag-0.5Cu flip chip solder joints at an ambient temperature of 150 °C. We observed mass protrusion on the chip side (hot end), indicating that Sn atoms moved to the hot end, and void formation on the substrate side (cold end). The diffusion markers also moved to the substrate side, in the same direction of the vacancy flux, indicating that the latter played a dominant role during the thermomigration process. The molar heat of transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The results reveal that some small Ag 3 Sn IMCs seemed to redistribute toward the cold side, as highlighted in the dashed line. It is believed that Ag atoms moved to the cold end and reacted with Sn to re-precipitate under the influence of a temperature gradient [5,13]. Another interesting finding is that appreciable Ni consumption was observed at the hot end; in particular, the Ni UBMs near the upperleft-hand corner at upper interface was remarkably consumed.…”
Section: Experimental Setup and Characterizationmentioning
confidence: 93%
See 1 more Smart Citation
“…The results reveal that some small Ag 3 Sn IMCs seemed to redistribute toward the cold side, as highlighted in the dashed line. It is believed that Ag atoms moved to the cold end and reacted with Sn to re-precipitate under the influence of a temperature gradient [5,13]. Another interesting finding is that appreciable Ni consumption was observed at the hot end; in particular, the Ni UBMs near the upperleft-hand corner at upper interface was remarkably consumed.…”
Section: Experimental Setup and Characterizationmentioning
confidence: 93%
“…In the study by Sawatzky [2], the hydrides were observed to reprecipitate at the cold side in the zirconium alloys. More recently, thermal gradient induced microstructural change and composition redistribution were found in the SnPb alloys [3][4][5], indicating that thermal gradient caused Pb atoms move from the hot end to the cold side whereas Sn atoms move in the opposite direction.…”
Section: Introductionmentioning
confidence: 97%
“…Ouyang et al [6] performed in situ observation of SAC305 solder joints under TM condition. They confirmed that Sn atoms migrate to the hot side, and the molar heat of transport of the Sn atoms is measured to -3.38 kJ/mol by marker displacement method.…”
Section: Introductionmentioning
confidence: 99%
“…Despite TM behavior in a plain solder joint being reported previously [14,15], up until the current time a systematic study of microstructural evolution and elemental redistribution in a composite solder interconnection containing enhancing particles involving a large temperature gradient is still absent.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the average temperature difference across the solder joint is evaluated as 1240 K/cm. According to previous studies [15], TM in Sn-based solder alloys can be triggered if the environmental temperature and the temperature gradient reach at least 100 °C and 1000 K/ cm, respectively. Based on the above-mentioned results, it is apparent that the obtained levels of environmental temperature and temperature gradient in the solder joint effectively meet the requirements for TM.…”
Section: Feasibility Evaluation Of Tm Setup and Samplementioning
confidence: 99%